An Analysis of Corruption Prevention in Jepara: The Integration of E-Government, Legislative Functions, Legal Integrity, and Local Wisdom - Haizul Ma’arif; Indah Sri Utari; Mumammad Junaidi (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study investigates a corruption prevention paradox in Jepara Regency, Indonesia, where massive financial crimes persist despite high Monitoring Center for Prevention (MCP) scores and robust Electronic-Government (E-Government) adoption. The research aims to deconstruct the failure of purely technocratic anti-corruption approaches by emphasizing the sociological context of human operators. Utilizing quantitative Path Analysis, this study examines the influence of Legislative Function, Legal Integrity, Local Wisdom, and E-Government Integration on Corruption Prevention. Data was acquired through structured Likert-scale questionnaires distributed to 226 respondents, comprising local government officials, legislative representatives (DPRD), governance experts, and cultural preservation figures. Findings reveal that while E-Government and legislation provide essential regulatory frameworks, Legal Integrity acts as a critical mediator. Furthermore, Local Wisdom, as measured through indicators of Ratu Kalinyamat's meritocratic leadership philosophy and the socio-cultural ethos of Jepara woodcarving, functions as a significant socio-cultural moderator that bridges the gap between theoretical regulation and actual bureaucratic behavior. The novelty of this research lies in its mathematical demonstration that integrating traditional cultural ethics fundamentally enhances the efficacy of modern anti-corruption systems. Ultimately, sustainable local corruption eradication requires a holistic synthesis of digital transparency, legislative accountability, and deep-rooted cultural ethics. These findings urge Indonesian regional governance policymakers to incorporate localized moral frameworks alongside technocratic oversight to achieve genuine bureaucratic reform.